New records of Protobranchia (Mollusca: Bivalvia) in the Peruvian Sea - Paredes, Carlos (2001)
The following species of Bivalvia have been recorded for the first time for Peruvian waters: Nucula (Nucula) iphigenia (Dall, 1908); Ennucula cardara (Dall, 1916); Nuculana (Nuculana) extenuata (Dall, 1897); Orthoyoldia panamensis (Dall, 1908). These bivalves were collected in the platform and continental slope down to depths of 864 meters.